Integrating free and open source tools and distributed modelling codes in GIS environment for data-based groundwater management. (September 2018) - Rossetto, Rudy; De Filippis, Giovanna; Borsi, Iacopo; Foglia, Laura; Cannata, Massimiliano; Criollo, Rotman; Vázquez-Suñé, Enric
Abstract: Integrating advanced simulation techniques and data analysis tools in a freeware Geographic Information System (GIS) provides a valuable contribution to the management of conjunctive use of groundwater (the world's largest freshwater resource) and surface-water. To this aim, we describe here the FREEWAT (FREE and open source software tools for WATer resource management) platform. FREEWAT is a free and open source, QGIS-integrated interface for planning and management of water resources, with specific attention to groundwater. The FREEWAT platform couples the power of GIS geo-processing and post-processing tools in spatial data analysis with that of process-based simulation models. The FREEWAT environment allows storage of large spatial datasets, data management and visualization, and running of several distributed modelling codes (mainly belonging to the MODFLOW family). It simulates hydrologic and transport processes, and provides a database framework and visualization capabilities for hydrochemical analysis. Examples of real case study applications are provided. Highlights: Information and Communication Technology provides robust tools for groundwater management. GIS facilitates the use of large datasets and complex modelling environments. FREEWAT is a free and open source QGIS plugin for groundwater management. FREEWAT integrates spatial and non-spatial data analysis tools and simulation codes. Application to case studies in EU and non-EU Countries demonstrates FREEWAT utility.